Transforming palm oil production: sustainable techniques and waste management strategies for Cameroon's smallholder farmers - Ayompe, Lacour M.; Nkongho, Raymond N.; Acobta, Ada N.; Masso, Cargele; Egoh, Benis N. (Frontiers in Sustainable Food Systems, 2025)
IntroductionThe palm oil sector is vital for Cameroon's smallholder farmers but is increasingly scrutinized for its environmental impacts, including deforestation, soil degradation, and waste mismanagement. Bridging productivity and sustainability demands integrated strategies that support farmer livelihoods while meeting global climate and conservation goals.MethodsWe conducted a systematic literature review and analytical synthesis of peer-reviewed studies, industry reports, and technical guidelines on Good Agricultural Practices (GAPs), Good Management Practices (GMPs), diversified cropping systems, fertilizer regimes, and waste valorization in oil palm systems. Drawing on this evidence base, we constructed two decision-support frameworks: one for sustainable palm oil production and another for circular-economy waste management.ResultsOur review confirms that adopting GAPs and GMPs such as soil conservation, optimized fertilizer application, and integrated pest management yields 10–20% gains in yield and income for smallholders, while intercropping enhances land-use efficiency, soil organic matter, and greenhouse-gas mitigation. The sustainable-production framework emphasizes no-deforestation in High Carbon Stock or High Conservation Value areas, prohibits slash-and-burn practices, and integrates incentives (e.g., carbon credits, subsidized inputs) to drive compliance. The waste-management framework demonstrates that palm oil mill residues and effluents can be transformed into organic fertilizers, biogas, bioethanol, and biocomposites, unlocking additional revenue streams and closing nutrient loops.DiscussionImplementing these frameworks requires strengthening certification schemes, capacity-building, and targeted smallholder support to overcome financial and technical barriers. By synergizing production efficiency, environmental safeguards, and waste valorization, Cameroon's smallholder sector can transition to a resilient, low-carbon model. Scaling these strategies promises to enhance farmer livelihoods, reduce sector-wide emissions by at least 25%, and contribute meaningfully to national climate-mitigation and biodiversity conservation goals.